'I use any pronouns, and I'm questioning everything else': transgender youth and the issue of gender pronouns. Issue 3 (4th May 2018) - McGlashan, Hayley; Fitzpatrick, Katie
Abstract: The nature of sex/ualities, genders and schooling has changed considerably over the last 20 years, with global political, social and cultural shifts bringing the lives of queer youth to the fore. Trans youth are now more visible and various kinds of support groups in schools (such as diversity support groups, queer groups and gay–straight alliances) have emerged. This article reports on a critical ethnographic study conducted with queer youth in a co-educational secondary school in Auckland, Aotearoa/New Zealand. The focus of the research was on exploring how LGBTQ students actively negotiate their identities in school. A particular issue of interest was how gendered pronouns (s/he, him, her) are used (both in and outside of schools). We consider how the naming of pronouns both disrupts the articulation between sex, gender and sexuality and also reinforces stable gender identities and binaries. This opens up new possibilities for the trans students to identify but also works to reinforce hierarchies and power relations. We employ the theoretical tools of Foucault (power and resistance) and Butler (the heterosexual matrix, intelligible subjects and performativity) to conceptualise and interpret the power relations evident in trans students' experiences of using gender pronouns.